SAT0207 ANTI-SSA/RO POSITIVITY AND CONGENITAL HEART BLOCK: OBSTETRIC AND FETAL OUTCOME IN A COHORT OF ANTI-SSA/RO POSITIVE PREGNANT WOMEN WITH AND WITHOUT AUTO-IMMUNE DISEASES FROM THREE ITALIAN TERTIARY REFERRAL CENTERS. (2nd June 2020) - Gerosa, M.; Fredi, M.; Andreoli, L.; Chighizola, C.; Argolini, L. M.; Donzelli, D.; Vojinovic, T.; Ramoni, V.; Bellis, E.; Trespidi, L.; Gazzola, F.; Ferrazzi, E.; et al.
Abstract : Background: neonatal lupus syndrome (NLS) is an acquired disease caused by the trasplacental passage of anti-SSA antibodies. Congenital heart block (CHB) represents the most serious manifestation of NLS. The rate of CHB in Anti-SSA positive pregnant women ranges from 1 to 5% in different studies Objectives: to retrospectively assess the prevalence of CHB in a cohort of anti-SSA positive pregnant women followed in 3 Italian tertiary centers Methods: pregnancies of anti-SSA positive women attending the pregnancy clinic of ASST Pini CTO/Policlinico Mangiagalli, Rheumatology Division of Spedali Civili, Brescia and Rheumatology Division of Ospedale S Matteo, Pavia from 2009 to 2019 were included. Patients underwent monthly clinical examination. Fetal heart rate was assessed weekly by Doppler ultrasound from 14 th to 26 th gestational week. On week 14 and 26, a fetal echocardiography was performed. A EKG was performed at birth Results: 351 prospectively followed pregnancies in 292 anti-SSA/Ro positive women were included. Table 1 reports diagnosis. None of the prospectively followed pregnancies were complicated by complete CHB. Seven additional patients were referred to our clinics after diagnosis of CHB and were subsequently found to be anti-SSA positive, reporting no symptoms of diseases. Considering the 7 additional pregnancies, the incidence of CHB was 1.9%. We observed 3 neonates (0.8%) with cutaneous NLS and 1 case of transient increase of liver enzymes. In another neonate, a 1 th degree A-V block was found after birth. A complete analysis of maternal and fetal outcome was possible in 244 cases (Table 2 ) and compared with 3158 unselected healthy controls. Among these 244 cases, 65% were taking hydroxychloroquine Conclusion: none of the patients prospectively followed in our centers before and during pregnancy developed complete CHB. If the 7 cases of anti-SSA positivity diagnosed after CHB detection were included in the analysis, the incidence of CHB was comparable to previous reports. Our data suggest that a strict follow up and proper treatment of anti-SSA positive patients with or without an autoimmune disease before and during pregnancy can reduce the risk of NLS. Further studies are warranted to confirm a possible protective role of anti-rheumatic treatments, including HCQ References: [1]Fredi M. Front Cardiovasc Med. 2019 Disclosure of Interests: Maria Gerosa: None declared, Micaela Fredi: None declared, Laura Andreoli: None declared, Cecilia Chighizola: None declared, Lorenza Maria Argolini: None declared, Davide Donzelli: None declared, Tamara Vojinovic: None declared, Véronique Ramoni: None declared, Elisa Bellis: None declared, Laura Trespidi: None declared, Federica Gazzola: None declared, Enrico Ferrazzi: None declared, Sonia Zatti: None declared, Fausta Benvenuti: None declared, Pier Luigi Meroni: None declared, Franco Franceschini: None declared, Carlomaurizio Montecucco: None declared, Rolando Cimaz: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB, Angela Tincani: None declared